The construction of indonesian maritime infrastructure through public private partnerships - M. Zaidun, Mas Rahmah, (Opción, 2019)
The study aims to investigate the construction of Indonesian maritime infrastructure through Public Private Partnerships via conceptual, statute and comparative approaches. As a result, the Implementation stage involves the project implementation including establishing the Project Company by the Project Sponsors, and the financing, construction, commissioning and operation of the project. In conclusion, the adoption of a maritime infrastructure specific PPP regime would also allow Indonesia to develop the human resource expertise that can assist with further construction of PPP management for the country.